Characterization of Serum Cytokine Patterns in Frequent-Exacerbation Asthma: Implications for Phenotyping and Management - Dao Ngoc Bang; Pham Dac The; Pham Thi Kim Nhung; Nguyen Tien Dung; Bach Quoc Tuan; Vu Minh Duong; Le Thi Dieu Hien; Ta Ba Thang (Advances in Respiratory Medicine)
(1) Background: Asthma exacerbations represent significant clinical events, however, the underlying inflammatory mechanisms and cytokine profiles in patients with frequent exacerbations remain incompletely understood; (2) Methods: In this prospective, cross-sectional study of 120 stable asthma patients, we compared the serum concentrations of eight key cytokines (IL-4, IL-12, IL-13, IL-17, IFN-α, IFN-γ, TNF-α, and IL-1β) between two groups: 60 patients with frequent exacerbations (≥ 2 events per year) and 60 matched controls with few exacerbations (1 event per year); (3) Results: Patients with frequent exacerbations showed significantly higher serum concentrations of IL-4 and IL-13 (p < 0.05), along with an increased prevalence of allergic history and comorbidities (chronic rhinosinusitis, GERD, OSA; all p < 0.05). The IgE levels correlated positively with IFN-α (rh = 0.26) and TNF-α (rh = 0.29), while the FeNO levels correlated with IL-17 (rh = 0.26) and IL-1β (rh = 0.33) (all p < 0.05); (4) Conclusions: Our findings identify a distinct cytokine signature in frequent exacerbators characterized by elevated IL-4 and IL-13 levels. The correlations between specific cytokines and established biomarkers suggest potential mechanisms underlying exacerbation susceptibility, which may inform targeted therapeutic strategies for this high-risk population.